Site-Selective C─H Bond Functionalization of Sugars; Angewandte Chemie; Vol. 64, iss. 19 - Stepanova E. V. Elena Vladimirovna; Shatskiy A. Andrey; Doroshenko I. A. Ivan Alekseevich (2025, 2025)
Title screen